Natural radiactivity from building materials in Spain - Pérez-Martínez, Manuel; Dueñas-Buey, Mª Concepción; Gordo Puertas, Elisa; Fernández Jiménez, Mª del Carmen; Cañete-Hidalgo, Sergio Andrés; Cabello Ganuza, María; Ruiz-Cruces, Rafael; Liger-Pérez, Esperanza; León-Reina, Laura (My University, 2015)
The industrial construction sector is very important in Spain. Building materials used in this industry are sources of radiation from natural radionuclides they contain. The European Commission published some recommendations to facilitate the trade of these materials in the E.U. The studies about this subject have increased notably during last years. This, probably, can be associated with the increase interest from natural radiation radiological risk on indoor exposure.
Keywords: Sustancias radiactivas; NORM; U-238, Th-232, K-40; Radiactivity materials